As transições de carreira de mulheres: a experiência do trabalhar e as barreiras de carreira - Berzin, Juliana (2022)
The changes in the world of work in the 21st century configure a reality of globalization and technological innovation, marked by the flexibilization and precariousness of work. Unpredictability and discontinuity characterize the new work relationships between individuals and organizations, making them less defined and stable. In a scenario of redefined work, transitions and choices throughout a career are amplified and the attention turns to the individual inserted in his/her context. The focus then broadens to those excluded from traditional career studies, including gender-related barriers. Thus, this thesis aims to analyze the experience of working and the career transition of women with different levels of professional qualification, from the perspective of Relational Theory of Working and The Psychology of Working Theory. The theories together allow a complementary analysis of the phenomenon, since the Relational Theory of Work conceptualizes work as part of a relational and contextualized experience, encompassing all areas of life, emphasizing the relational aspects of women's careers. Work Psychology, on its turn, proposes an understanding of the barriers to decent work and proposes the analysis of gender as a determining factor, emphasizing the level of choices and career volition. A qualitative, descriptive, multiple-case study was conducted. We interviewed women between 25 and 49 years old, with a history of career transition in their professional trajectory in the last five years, living in the South and Southeast regions, divided into two groups. In the first group we interviewed women with a professional profile with higher education (university education and graduate studies) and in the second group we interviewed women with a professional profile non-higher education group. In each group 12 women were interviewed, according to data saturation criteria. The narrative-episodic interview was used and the data analysis procedure was carried out by means of thematic categorical content analysis. The analysis of the results suggests that the gender dimension is essential to the understanding of women's careers and the experience of working, the differences between the different profiles are related to the higher level of resources to face the challenges, including the necessary social support. Career transitions are present in the interviews, with shorter cycles observed in the group without professional training, and career adaptability is a fundamental psychosocial resource for the development of new strategies. Gender-related barriers represent challenging obstacles, being a conditioning factor for working, even determining the limits of women's careers. Despite the difficulties, volition as a perception of choice is present and the need for self-determination is what motivates women's career transition. The relational aspects inside and outside of work, as interconnected dimensions, are expressed by the social connection to work and the social support needed for women's career development. At work, when professional relationships are supportive, they are a source of learning and opportunity and a sense of belonging. The broader relational context involves the family, present in the decisions, especially after motherhood. We conclude that decent work in the experience of women is characterized as an ideal to be reached, with attributes peculiar to the Brazilian context. The constant movement based on the need to reinvent oneself, to build new alternatives, to eliminate suffering at work, points to a transformation of what is possible towards the desired ideal. In this way, besides being relational, working is in a constant movement of adaptability, with the goal of experiencing well-being and fulfillment at work.